2023
DOI: 10.1155/2023/3081660
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Trends in Demographic, Laboratory, Imaging, and Clinical Outcomes of ICU-Hospitalized COVID-19 Patients

Abstract: Background. COVID-19 has led to significant hospitalization and intensive care unit admission rates. The demographic parameters of COVID-19 patients, such as age, underlying illnesses, and clinical symptoms, substantially influence the incidence and mortality of these individuals. The current study examined the clinical and demographic characteristics of COVID-19 intensive care unit (ICU) patients in Yazd, Iran. Methods. The descriptive-analytical cross-sectional study was conducted on ICU patients with a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Gholinataj Jelodar et al (2023), in a cross-sectional study, evaluated the NLR parameter of ICU COVID-19 patients and demonstrated a significative difference between the groups of survivors and non-survivors. NLR was a risk factor in the multivariate logistic regression (OR 1.045, 95% CI: 1.012–1.079, p = 0.007) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gholinataj Jelodar et al (2023), in a cross-sectional study, evaluated the NLR parameter of ICU COVID-19 patients and demonstrated a significative difference between the groups of survivors and non-survivors. NLR was a risk factor in the multivariate logistic regression (OR 1.045, 95% CI: 1.012–1.079, p = 0.007) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%